Protective role of gout against colorectal cancer: a Mendelian randomization study - Xia Pan; Yong’an Liu; Xiaoming Zhang; Yan Meng (Discover Oncology)
Abstract Background The battle against cancer is often hindered by the complex mechanisms of drug resistance, a key challenge in treatment. In this context, the inflammatory condition gout, characterized by hyperuricemia, has shown potential protective effects against colorectal cancer (CRC). This study explores the causal relationship between gout and CRC using Mendelian randomization (MR) analysis to contribute insights into tumor biology and resistance mechanisms. Methods A two-sample MR analysis was conducted using genetic instruments for gout derived from genome-wide association studies (GWAS) in both discovery and replication cohorts. The primary genetic instruments included single nucleotide polymorphisms (SNPs) associated with serum uric acid levels. There are 7 and 21 SNPs used as genetic proxies for gout in the two independent cohorts. The inverse-variance weighted (IVW) method was employed as the main analysis, with robustness assessed through sensitivity analyses, including Cochran’s Q test, MR-Egger intercept, and MR-PRESSO tests. Results MR analysis suggested a protective effect of genetically predicted gout against CRC (Odds Ratio [OR] = 0.957, 95% Confidence Interval [CI] 0.919–0.997, P = 0.037) in the discovery cohort. These findings were replicated in the replication cohort (OR = 0.018, 95% CI 0.002–0.201, P = 0.001). In the sensitivity analysis, Cochran’s Q test found no significant heterogeneity, and neither the MR-Egger intercept nor the MR-PRESSO tests provided evidence of significant horizontal pleiotropy, supporting the robustness of the causal inference. Conclusion This study provides genetic evidence that gout may mitigate CRC risk through mechanisms potentially related to uric acid's antioxidant and immune-modulating properties.